Dynamic simulation of a Vacuum Packed Particles Torsional Damper with ABS-NBR particle mixtures using a modified Bouc-Wen model - Rodak, Dominik; Żurawski, Mateusz; Zalewski, Robert (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
Vacuum Packed Particles Torsional Dampers (VPPTDs) are adaptive devices capable of providing tunable damping through the adjustment of underpressure inside a granular-filled chamber. Despite their promising applications in vibration control, accurately modeling their highly nonlinear and hysteretic behavior remains a significant challenge. This paper shows a modified Bouc-Wen model that incorporates an additional nonlinear stiffness term and a dry friction component to better represent the torque-angular displacement relationship under varying operational conditions. Quasi-static experiments were conducted on a dedicated test stand with harmonic excitation (±10◦) across frequencies from 0.0 to 0.8 Hz and underpressures ranging from 0.00 to 0.09 MPa. Various granular mixtures composed of Acrylonitrile Butadiene Styrene (ABS) and Nitrile Butadiene Rubber (NBR) particles in volume ratios of 1:0, 3:1, 1:1, 1:3, and 0:1 were investigated. The shape and area of the hysteresis loops were found to depend strongly on both the mixture composition and the vacuum level. Model parameters were identified using evolutionary algorithms and expressed as functions of underpressure, allowing the simulation of pressure-dependent damping and stiffness behavior. Dynamic simulations based on the identified models confirmed that adjusting the vacuum level effectively changes the system dynamic response. The results demonstrate that the proposed model reliably captures the complex hysteretic behavior of VPPTDs and confirms the feasibility of employing underpressure as an effective control variable in adaptive damping applications.